Crystallization and preliminary X-ray diffraction experiments of arylmalonate decarboxylase from Alcaligenes bronchisepticus - Nakasako, Masayoshi (International Union of Crystallography, 2008)

(untitled)
Arylmalonate decarboxylase catalyses the enantioselective decarboxylation of α-aryl-α-methylmalonates to produce optically pure α-arylpropionates. The enzyme was crystallized with ammonium sulfate under alkaline pH conditions with the aim of understanding the mechanism of the enantioselective reaction. X-ray diffraction data collected to a resolution of 3.0 Å at cryogenic temperature showed that the crystals belonged to the orthorhombic space group P2(1)2(1)2(1), with unit-cell parameters a = 83.13, b = 99.62, c = 139.64 Å. This suggested that the asymmetric unit would contain between four and six molecules. Small-angle X-ray scattering revealed that the enzyme exists as a monomer in solution. Thus, the assembly of molecules in the asymmetric unit was likely to have been induced during the crystallization process.